Reciting the Quran using symbols: a global learning approach / Suzana Baharudin ... [et al.]. - Baharudin, Suzana; Hamka Kamaroddin, Juliana; Roslim, Norwati; Ahmad, Suzana (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Symbols play a crucial role in communication by transcending language barriers and enhancing understanding. In multimedia, they appear as visual icons that convey clear and quick messages. In religious texts like the Quran, and in music, symbols are equally important. These elements significantly influence how the brain processes and interprets information, engaging unique cognitive functions during activities such as Quranic recitation or reading music (Al-Galal et al., 2016). With the global Muslim population expected to reach 2.03 billion by the end of 2024, Islam will remain the second-largest religion. This growing community spans continents, emphasizing the need for accessible tools to learn Quranic recitation. Correct recitation, governed by tajweed rules, is a fundamental duty in Islam, ensuring proper pronunciation and articulation for a valid and reverent recitation (WorldPopulationReview.com, 2024).